2018
DOI: 10.15666/aeer/1602_20592072
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Physiological Indices of Waterlogging Tolerance of Different Maize Varieties in South China

Abstract: Maize is extremely sensitive to waterlogging stress. A pot experiment was conducted to study the morpho-physiological characteristics of 18 differrent maize cultivars (widely grown in South China) under waterlogging stress at seedling stage. Results showed that maize shoot growth was inhibited in terms of plant height and dry weight whilst leaf chlorophyll contents were also decreased under waterlogging stress. Root length, root hairs, root surface area and root volume were also declined under waterlogged cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 27 publications
(40 reference statements)
2
16
0
Order By: Relevance
“…Several crop species exhibit their ability to survive under the flooded or WL condition for short or even longer durations by activating antioxidant defense systems (Table 3). Li et al [207] exposed 18 maize genotypes to WL conditions. After 2 d of WL stress, 19-57% higher SOD activity was observed in 12 genotypes, 19.16-106.96% higher POD activity was found in 13 genotypes, while 26-57% higher CAT activity was found in only 9 genotypes.…”
Section: Antioxidant Defense In Plants Under Floodingmentioning
confidence: 99%
“…Several crop species exhibit their ability to survive under the flooded or WL condition for short or even longer durations by activating antioxidant defense systems (Table 3). Li et al [207] exposed 18 maize genotypes to WL conditions. After 2 d of WL stress, 19-57% higher SOD activity was observed in 12 genotypes, 19.16-106.96% higher POD activity was found in 13 genotypes, while 26-57% higher CAT activity was found in only 9 genotypes.…”
Section: Antioxidant Defense In Plants Under Floodingmentioning
confidence: 99%
“…Several genotypes of maize were subjected to waterlogging stress. Genotypes withstanding the waterlogging stress displayed higher SOD, POD, and CAT activities ( Li et al, 2018 ). Similarly, induced SOD and CAT activities were observed in the Sorghum bicolor waterlogging-resistant lines JN01 and JZ31 ( Zhang R. et al, 2019 ).…”
Section: Damage By Reactive Oxygen Speciesmentioning
confidence: 99%
“…Studies have revealed flooding-induced increments of LPO, ROS overgeneration, and other oxidative damages in different crops. Some cereal crops, for example, Z. mays L., S. bicolor L., Hordeum vulgare L., et cetera, showed a remarkable increase in LPO and accumulation of H 2 O 2 , O 2 •− , and • OH under different durations of WL condition [ 117 , 118 , 119 ]. Li et al [ 117 ] chose eighteen maize genotypes to evaluate the WL (2 d)-induced changes in LPO.…”
Section: Oxidative Stress Under Abiotic Stressmentioning
confidence: 99%
“…Some cereal crops, for example, Z. mays L., S. bicolor L., Hordeum vulgare L., et cetera, showed a remarkable increase in LPO and accumulation of H 2 O 2 , O 2 •− , and • OH under different durations of WL condition [ 117 , 118 , 119 ]. Li et al [ 117 ] chose eighteen maize genotypes to evaluate the WL (2 d)-induced changes in LPO. They observed that MDA content increased in only in four genotypes, compared to control plants, but declined in other genotypes, which might be due to the scavenging of ROS by antioxidant enzymes.…”
Section: Oxidative Stress Under Abiotic Stressmentioning
confidence: 99%